A Guanosine‐Quadruplex Hydrogel as Cascade Reaction Container Consuming Endogenous Glucose for Infected Wound Treatment—A Study in Diabetic Mice. Issue 7 (22nd January 2022) - Li, Yuanfeng; Su, Linzhu; Zhang, Yongxin; Liu, Yong; Huang, Fan; Ren, Yijin; An, Yingli; Shi, Linqi; van der Mei, Henny C.; Busscher, Henk J.
Abstract: Diabetic foot ulcers infected with antibiotic‐resistant bacteria form a severe complication of diabetes. Antimicrobial‐loaded hydrogels are used as a dressing for infected wounds, but the ongoing rise in the number of antimicrobial‐resistant infections necessitates new, nonantibiotic based designs. Here, a guanosine‐quadruplex (G4 )‐hydrogel composed of guanosine, 2‐formylphenylboronic acid, and putrescine is designed and used as a cascade‐reaction container. The G4 ‐hydrogel is loaded with glucose‐oxidase and hemin. The first cascade‐reaction, initiated by glucose‐oxidase, transforms glucose and O2  into gluconic acid and H2 O2 . In vitro, this reaction is most influential on killing Staphylococcus aureus or Pseudomonas aeruginosa in suspension, but showed limited killing of bacteria in biofilm‐modes of growth. The second cascade‐reaction, however, transforming H2 O2  into reactive‐oxygen‐species (ROS), also enhances killing of biofilm bacteria due to hemin penetration into biofilms and interaction with eDNA G‐quadruplexes in the biofilm matrix. Therewith, the second cascade‐reaction generates ROS close to the target bacteria, facilitating killing despite the short life‐time of ROS. Healing of infected wounds in diabetic mice proceeds faster upon coverage by these G4 ‐hydrogels than by clinically common ciprofloxacin irrigation. Moreover, local glucose concentrations around infected wounds decrease. Concluding, a G4 ‐hydrogel loaded with glucose‐oxidase and hemin is a good candidate for infected wound dressings, particularly in diabetic patients. Abstract : A supramolecular guanosine‐quadruplex (G4 )‐hydrogel containing glucose oxidase and hemin provides a cascade‐reaction container suitable as an antibacterial dressing for infected wounds. The cascade‐reaction in the G4 ‐hydrogel generates reactive‐oxygen‐species inside an infectious biofilm from endogenous glucose, killing multidrug resistant bacteria on a nonantibiotic basis, yielding faster healing of infected wounds, and reducing local glucose levels in diabetic mice.